Loess mantle spatial variability and soil horizonation, southern Wisconsin, USA - Jacobs, Peter M.; Mason, Joseph A.; Hanson, Paul R. (Quaternary International, 2012)
Loess is an important Quaternary sediment that records evidence of landscape instability in sediment source areas and landscape stability in accumulation areas. In Wisconsin, USA loess mantles glaciogenic deposits dating to the last glaciation, but the landscape distribution and effects of the loess mantle on soil formation have received very little attention. This study investigates the influence of glacial landforms on the spatial pattern of loess thickness and how the presence or absence of a loess mantle overlying glaciogenic sediments has influenced soil profile morphology, namely thickness and nature of horizonation. Loess thickness follows systematic trends along hillslopes, with slope percentage explaining most loess thickness variation between summit and backslope positions. In the presence of a loess mantle, solum and Bt horizon thickness is proportional to the thickness of the loess mantle in well-drained profiles. In the absence of a loess mantle, landscape and sediment characteristics that control permeability and water throughflow appear to be the most important determinants of profile characteristics. The loess mantle modulates soil formation above the lithologic discontinuity with sandy calcareous glacial sediments by controlling soil water behavior and having physical and chemical characteristics conducive to transformation to soil genetic horizons.
id: 2151